Exploring the Purpose of Agricultural Technical Schools in Haiti - Christelle M. Calixte; Grady T. Roberts; J. C. Bunch (Journal of International Agricultural and Extension Education, 2019)
Haiti is a country which suffers from food insecurity, therefore, agricultural production and productivity are important to ensure availability of food for the Haitian population. Dissemination of best agricultural practices amongst farmers is crucial, and extension agents bring the scientific discoveries into the rural communities. In Haiti, extension activities are primarily conducted by graduates from agricultural TVETs. However, little is known about the current situation of Haitian TVET within the agricultural system. This study is a basic qualitative research which used constructivism, and backwards design as theoretical framework to explore the purpose of TVET within the Haitian agricultural system. Individual interviews to schools’ directors and teachers, and focus groups conducted with students revealed that respondents thought that TVET helped in students’ social mobility by (a) providing training to disadvantaged youth, (b) helping them get financial independence sooner, (c) provide a path towards higher education, or (d) entrepreneurship; it also allows them to build necessary (e) networking and (f) a reputation for their future. On the other hand, agricultural TVET in Haiti had an important role in improving local communities by (a) ensuring rural development and (b) reducing rural outmigration and poverty. Finally, TVET was also crucial within the agricultural extension system because graduates were responsible for (a) providing technical assistance to farmers, (b) improving production practices, (c) helping protect the environment, and (d) training farmers.
Keywords: Haiti; technical school; training